Resident Microbiome of Kidney Tumors - Kovaleva, Olga; Podlesnaya, Polina; Gratchev, Alexei (Oncology Reviews, 2024)
Emerging research has uncovered the significance of microbiota in carcinogenesis, with specific bacterial infectious agents linked to around 15% of malignant tumors. This review is focused on the resident kidney microbiome, its composition, and alterations in various diseases. Recent studies have shown that bacteria can infiltrate the kidney, with differences between normal and tumor tissue. These studies have identified distinctive microorganisms unique to both conditions, hinting at their potential clinical relevance. Research into the kidney microbiome diversity reveals differences in tumor tissue, with specific taxa associated with different histological types. Notably, the alpha diversity indices suggest variations in bacterial content between tumor and normal tissue, offering insights into potential diagnostic and prognostic use of these markers. Better studied is the impact of the gut microbiome on therapy efficacy in malignant kidney tumors. Antibiotics, which can alter the gut microbiome, have been linked to survival outcomes in patients receiving targeted therapy and immunotherapy. The findings suggest that the uncontrolled use of antibiotics may not only contribute to bacterial resistance but also disrupt the normal microbiome, potentially influencing the development of oncological diseases. In-depth investigation into the resident kidney microbiome is essential for addressing fundamental and practical aspects of kidney tumor development.